20th Congress of the European Burns Association (EBA) - Nadia Depetris; Alette De Jong; Clemens Schiestl; Franck Duteille; Jill Meirte; Joan P. Barret-Nerin; Paul Van Zuijlen; Jyrki Vuola; Stian Almeland (MDPI AG, 2023)
Abstracts of the plenary and special interest sessions, workshops, and oral and poster presentations of the 20th EBA Congress in Nantes, France from 6-9 September 2023.